2021
DOI: 10.1002/hep4.1801
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cholesterol‐Associated Steatohepatitis in the Development of NASH

Abstract: The rising prevalence of nonalcoholic fatty liver disease (NAFLD) and NAFLD-related cirrhosis in the United States and globally highlights the need to better understand the mechanisms causing progression of hepatic steatosis to fibrosing steatohepatitis and cirrhosis in a small proportion of patients with NAFLD. Accumulating evidence suggests that lipotoxicity mediated by hepatic free cholesterol (FC) overload is a mechanistic driver for necroinflammation and fibrosis, characteristic of nonalcoholic steatohepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
98
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(100 citation statements)
references
References 179 publications
(266 reference statements)
0
98
0
2
Order By: Relevance
“…Excess hepatic cholesterol has been shown to promote NASH in a variety of animal models, ( 14 , 16 , 21 , 28 , 29 ) through mechanisms involving endoplasmic reticulum (ER) stress, mitochondrial dysfunction, development of toxic oxysterols, or stabilization of the transcription factor TAZ. ( 30 ) We also demonstrated that in murine models of NASH driven by high‐fat, high‐cholesterol diets, excess cholesterol crystallizes in hepatocyte lipid droplets, and these cholesterol crystals might promote necroinflammation in NASH. ( 14 , 15 , 16 , 17 ) Here we also demonstrate increased hepatic free cholesterol and cholesterol crystallization in the Pcsk9 KO mice on 0.75% dietary cholesterol together with formation of “crown‐like structures” of CD68‐positive macrophages that surround and process hepatocytes and lipid droplets with cholesterol crystals (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Excess hepatic cholesterol has been shown to promote NASH in a variety of animal models, ( 14 , 16 , 21 , 28 , 29 ) through mechanisms involving endoplasmic reticulum (ER) stress, mitochondrial dysfunction, development of toxic oxysterols, or stabilization of the transcription factor TAZ. ( 30 ) We also demonstrated that in murine models of NASH driven by high‐fat, high‐cholesterol diets, excess cholesterol crystallizes in hepatocyte lipid droplets, and these cholesterol crystals might promote necroinflammation in NASH. ( 14 , 15 , 16 , 17 ) Here we also demonstrate increased hepatic free cholesterol and cholesterol crystallization in the Pcsk9 KO mice on 0.75% dietary cholesterol together with formation of “crown‐like structures” of CD68‐positive macrophages that surround and process hepatocytes and lipid droplets with cholesterol crystals (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…PLIN5 promotes lipid storage [ 69 ], and it is also increased in human steatosis [ 70 ]. Triglycerides mainly represent a “safe” storage for FA [ 50 ], whereas the accumulation of other lipotoxic lipids, such as cholesterol, FA, diacylglycerol, and ceramides, leads to cellular dysfunction [ 71 , 72 ]. Cholesterol accumulates in the liver when the total sum of the pathways involved in cholesterol synthesis and uptake exceeds the pathways involved in cholesterol removal [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data supporting this possibility is supported by in vitro results. The pathophysiology of NASH is very complex and many cell types within the liver are involved at multiple levels [ 34 ]. In whole liver, the factors measured by QPCR were IL-6, TNF-α, and TGF-β.…”
Section: Discussionmentioning
confidence: 99%